2021
DOI: 10.3390/cancers13030519
|View full text |Cite
|
Sign up to set email alerts
|

Brain Metastases from Uterine Cervical and Endometrial Cancer

Abstract: Reports on brain metastases (BMs) from uterine cervical carcinoma (CC) and uterine endometrial carcinoma (EC) have recently increased due to the development of massive databases and improvements in diagnostic procedures. This review separately investigates the prevalence, clinical characteristics, clinical presentation, diagnosis, treatment, and prognosis of BMs from CC and uterine endometrial carcinoma EC. For patients with CC, early-stage disease and poorly differentiated carcinoma lead to BMs, and elderly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 166 publications
(704 reference statements)
0
14
0
1
Order By: Relevance
“…Local disease control has been more successful in the combined approach but OS outcomes were not better [28][29][30]. As a result, there is no consensus on the most effective treatment and patient-tailored therapy seems to be the most logical approach [31]. In this cohort, SRS was used alone or in combination in approximately 25% of patients.…”
Section: Discussionmentioning
confidence: 92%
“…Local disease control has been more successful in the combined approach but OS outcomes were not better [28][29][30]. As a result, there is no consensus on the most effective treatment and patient-tailored therapy seems to be the most logical approach [31]. In this cohort, SRS was used alone or in combination in approximately 25% of patients.…”
Section: Discussionmentioning
confidence: 92%
“…A study done by Piura and Piura suggested that out of all gynaecological cancers, the incidence of brain metastasis of ovarian malignancy is 1.2% which is twice the incidence associated with cervical or endometrial cancer. 3 The most common histologic subtype of ovarian carcinoma associated with brain metastasis is the serous type, followed by mixed epithelial, endometrioid adenocarcinoma, mucinous, undifferentiated, and clear cell type. Some studies have demonstrated the correlation between germline mutations of BReast CAncer gene 1 (BRCA-1) mutations and incidence of brain metastases in ovarian carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…4 In the brain, the cerebrum is the most common site for metastases, followed by the cerebellum, and leptomeninges. 3 The frontal lobe is the most commonly involved area. 4 Symptoms of brain metastases include headaches, nausea, vomiting, confusion, dizziness, decreased mental status, general or extremity weakness, urinary incontinence, gait disturbance, ataxia, visual disturbance including diplopia, photophobia, speech impairment, syncope, and seizures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported by a recent study that patients with cervical cancer, poorly differentiated carcinoma and early stage disease lead to brain metastases; among patients with endometrial cancer, high grade carcinoma and advanced stage disease are high risk for brain metastases [ 25 ]. In our study, most patients of uterine cancer developed distant metastases were those with undifferentiated tumor group; there were no significant differences in differentiation grade among the cervical cancer or ovarian cancer patients developing distant metastases.…”
Section: Discussionmentioning
confidence: 99%